Comparative investigation of ultrasonic cavitation erosion for different engineering materials - Volkov-Husović, Tatjana; Martinović, Sanja; Vlahović, Milica; Alil, Ana; Dimitrijević, Bojan; Ivanić, Ivana; Pavkov, Vladimir (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Engineering materials are often exposed to various extremely harsh surroundings such as high temperatures and/or pressure, thermal shocks, aggressive solutions, or cavitation erosion. The phenomenon of cavitation erosion might be expected in conditions of fluid-flowing where the parts of equipment include turbine blades, high-speed propellers, or pump parts. Such conditions usually cause surface degradation with defects in the form of pits and fractures, resulting in strength deterioration with a potential risk of failure, as well as a reduction in the materials' lifespan that requires additional expenses for failure analysis, repair, and/or replacement of parts. This paper will present the main results regarding the study on cavitation erosion resistance of two different engineering materials, austenitic stainless steel 316L and CuAlNi shape memory alloy (SMA). Cavitation erosion testing was carried out using an ultrasonic vibratory method with a stationary sample. The comparison of the behavior between these two materials in cavitation erosion conditions will be shown based on the results of mass loss and analysis of the pits formed over time. Using image analysis tools, the surface damage levels were quantified. Detailed analyses revealed that SMA exhibited superior in terms of resistance and behavior compared to stainless steel.
Keywords: Cavitation erosion; 316L steel; CuAlNi SMA; Image analysis